Isolation, structure elucidation and anticancer activity from Brevibacillus brevis EGS 9 that combats Multi Drug Resistant actinobacteria. (February 2018) - Arumugam, T.; Senthil Kumar, P.; Hemavathy, R.V.; Swetha, V.; Karishma Sri, R.
Abstract: Actinobacteria is the most widely distributed organism in the mangrove environment and produce a large amount of secondary metabolites. A new environmental actinobacterial stain exhibited strong antimicrobial activity against vancomycin and methicillin resistant actinobacteria. The active producer strain was found to be as Brevibacillus brevis EGS9, which was confirmed by its morphological, biochemical characteristics and 16S rRNA gene sequencing. It was deposited in NCBI GeneBank database and received with an accession number of KX388147. Brevibacillus brevis EGS9 was cultivated by submerged fermentation to produce antimicrobial compounds. The anti-proliferative agent was extracted from Brevibacillus brevis EGS9 with ethyl acetate. The bioactive metabolites of mangrove actinobacteria was identified by Liquid chromatography with mass spectrometry analysis. The result of the present investigation revealed that actinobacteria isolated from mangroves are potent source of anticancer activity. The strain of Brevibacillus brevis EGS9 exhibited a potential in vitro anticancer activity. The present research concluded that the actinobacteria isolated from mangrove soil sediment are valuable in discovery of novel species. Graphical abstract: Image 1 Highlights: Isolation and screening of potential actinobacteria from mangrove soil. Potentially active strain was identified based on 16th rRNA sequences. Active strain was cultured on fermentation media and extracted bioactive metabolites. GC-MS chromatogram showed the presence of 30 major bioactive metabolites in the ethyl acetate extract. Crude extract of ethyl acetate proven significant anticancer activity on HepG2 cell line.